Bone mineral density, microarchitectural and mechanical alterations of osteoporotic rat bone under long-term whole-body vibration therapy. (January 2016) - Xie, Pengfei; Tang, Zhurong; Qing, Fangzhu; Chen, Xuening; Zhu, Xiangdong; Fan, Yujiang; Yang, Xiao; Zhang, Xingdong
Abstract: Low-magnitude, high-frequency whole body vibration (WBV) is receiving increasing interest as a non-pharmacological anti-osteoporosis approach. However, the long-term effect of WBV therapy is seldom studied. In this study, the efficacy of 16-week WBV (0.3 g, 30 Hz) on bone mineral density (BMD), microarchitectural parameters and mechanical properties of ovariectomized rat femur were examined by in vivo peripheral quantitative computed tomography (pQCT), ex vivo micro-computed tomography (µCT), dynamic mechanical analysis (DMA) and fracture test. To the best of our knowledge, 16 weeks of WBV administration (20 min/day) is currently the longest duration on rodent. The longitudinal BMD change showed that positive effect of WBV on ovariectomized rat femoral neck diminished with prolonged administration duration. In addition, 16-week of WBV treatment was found to cause significantly reduction in the mean BMD, trabecular BMD (Tb.BMD), trabecular bone volume ration (BV/TV), trabecular number (Tb.N) and maximum load in femoral neck of ovariectomized rat. Metaphyseal Tb.BMD and BV/TV were also significantly decreased in WBV treated ovariectomized group than non-treated controls. Whole-femur DMA was demonstrated as a sensitive tool in distinguishing osteoporotic femur from healthy aged-matched controls, in terms of decreased storage modulus ( E ′) and loss factor (tan δ ). However, E ′ and tan δ are not enhanced by 16-week WBV treatment. Together, these findings indicate that administration duration played an important role in the effect of WBV. 16-week WBV may exacerbate trabecular bone loss in ovariectomized rat femur, especially in trabecular-rich femoral neck region. An optimal WBV protocol including administration duration should be established prior to long-term clinical practice.